Bridgestone's new tyre for all seasons: CITY EDITION - Small, Adrian (The Irish times, 2004)
We were recently invited by Bridgestone to test its new Hypersport road tyre, the Battlax BT-014, at the Circuito De Almeria racetrack in southern Spain. This is the tyre to replace the Battlax BT-010 and Battlax BT-012 products. Bridgestone claims that it brings all-round improvements in wet and dry handling, grip, stability, durability and rider appeal. New tread compounds and carcass construction are used in both front and rear models - the rear has what's called cap-and-base construction which should provide effective shock absorption. Front and rear groove patterns have been designed to reduce deformation under extreme usage and provide efficient water drainage and lower noise levels. The rear tyre has also been stiffened to give greater stability. So, all in all, the Bridgestone BT-014 is an excellent road- going tyre. It provides the grip, stability and comfort a sportsbike rider needs in both wet and dry conditions. It could be used on a track day but we would suggest going for a more track developed tyre.